PENGGUNAAN ANGGARAN DAN GAYA KEPEMIMPINANN SEBAGAI PEMODERASI HUBUNGAN PERUBAHAN STRATEGIK DENGAN KINERJA ORGANISASI - Suhaeli, Dahli (Universitas Muhammadiyah Magelang, 2008)
This research aim to test influence of strategic change to organizational performance at company using budegt by interactive compared to company using budget diagnostically.Second target is to know influence of strstegic change to organizational performance at company using style leadership of consideration with company using style leadership of structure initiating. Organizational performance represent a measuring instrument used to measure storey, level efficacy of management. Company often make a change strategic to reach optimal performance. This research take manufacturing business sample exist in Magelang, by propagating equated to middle storey: level manager from each company. sample selected with method of convenience sampling, and got by 40 respondent. Result of research express taht strategic change have an effect on positive to performance when company use budget by interactive. Examination to both hypothesis expressing taht srategic change will be more have an effect on when company use style leadership of consideration tahn structure initiating. As narrow: tight as research region which only in Magelang cause result of this is reseach less earn generalizing for broarder region, so taht for research hereinafer shall be conducted by taking sample with broarder region.